Impact of climatic abnormities and mitigating technologies on pigeonpea (Cajanus cajan) in central India - SINGH, Y P (The Indian Journal of Agricultural Sciences, 2022)
A study was carried out on changes in climate; area and productivity of pigeonpea (Cajanus cajan L.) over aperiod of three decades (1982–2016), and impact of climatic abnormalities and mitigation technologies on yield andeconomic benefits was seen. Long-term data on climate change showed that there is a trend of minimum and maximum temperature rise and a decrease in monthly total rainfall in summer and rainy season, while it increases in winter. Study also revealed the prominent disparity in area and productivity of pigeonpea of all agro-climatic zones of Madhya Pradesh (MP) and Chhattisgarh (CG). The absolute change (AC) and relative change (RC) in area of pigeonpea in MP and CG states increased by 34.66 thousand ha and 16.2% and increased productivity by 243.3 kg/ha and 65.4% compared with base years, respectively. Like-wise maximum AC in productivity was at Central Narmada Valley (CNV) and minimum at CG plains, while RC in productivity was maximum increased in Gird region and minimum in CG plains compared to base years. The crop sowing on bed with broad bed furrow (BBF) increased seed yield by 18.2% compared to flat land sowing method. The Fusarium wilt infestation was reduced with resistant cultivar along with seed treatment with Trichoderma harzianum and BBF sowing impacting on yield by 26.2%, whereas increased by 20.7% with control of phytophthora blight resistant cultivar sowing on BBF after seed treatment with Trichoderma viride, compared with existing practices (EP). Similarly control of pod borer with the use of IPM technology enhanced seed yield by 42.2% compared with EP. Results showed that adoption of improved techniques for mitigation of climatic abnormalities gave higher productivity, net returns and B:C ratio compared to EP.